The Role of Sports in Reducing Stress and Anxiety in Women: A Quantitative Analysis Among Physical Education Students - Nimrot Manalu Nimrot Manalu; Miftahul Ihsan; Andes Martua Harahap; Santa Nunut Hutasoit; Ebenezer Sinulingga; Yosep Vieri Manurung; Khalik Alamsyah; Raja Ferdinan Aritonang; Hizkia Kaesar Agustinus Marpaung (Ikatan Sarjana Olahraga Republik Indonesia (Kabupaten Kampar), 2025)
Objectives: Stress and anxiety disorders disproportionately affect women, with prevalence rates significantly higher than in men. Physical activity and sports participation have emerged as promising non-pharmacological interventions for mental health management. This research aimed to investigate the effectiveness of sports participation in reducing stress and anxiety levels among female physical education students and to examine the relationship between different types of sports activities and psychological well-being outcomes. Methods: A cross-sectional quantitative study was conducted with 180 female Physical Education students from Universitas Negeri Medan, Indonesia. Participants completed the Perceived Stress Scale (PSS-10) and the Generalized Anxiety Disorder 7-item scale (GAD-7). Sports participation was assessed through a structured questionnaire measuring frequency, duration, and type of activities. Data were analyzed using SPSS version 28.0. Results: Results indicated a significant negative correlation between sports participation frequency and both stress (r = -0.67, p < 0.001) and anxiety levels (r = -0.72, p < 0.001). Participants engaging in sports ≥5 times per week showed 43% lower stress scores and 38% lower anxiety scores compared to those participating <2 times per week. Team sports demonstrated superior anxiety reduction compared to individual sports (p < 0.05). Conclusion: Sports participation significantly reduces stress and anxiety levels in women, with frequency and type of activity being crucial factors. These findings support the integration of structured sports programs in women's mental health interventions.